Effect of photoionized plasma and EUV induced surface modification on physico-chemical properties and cytocompatibility of PLLA - J. Czwartos; B. Budner; A. Bartnik; W. Kasprzycka; H. Fiedorowicz (eXPRESS Polymer Letters)
In this work, low-temperature photoionized plasma, induced in N2 by extreme ultraviolet (EUV) pulses, was used for surface modification of poly(L-lactic acid) (PLLA). Polymer samples were irradiated with 100, 200, and 300 pulses at a 10 Hz repetition rate. The physical and chemical properties of PLLA samples were examined using atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS). The human dermal fibroblast adult cells (NHDF-Ad) were used for the cell culture and viability tests on modified PLLA surfaces. The N2-plasma and EUV treatment caused alteration of the surface morphology resulting in increased surface roughness, incorporation of nitrogen atoms, and appearing of new functional groups on the surface. Cell culture results showed an increase in the number of fibroblasts attached to the modified surfaces compared to the pristine PLLA. The modified surfaces demonstrated high cell viability and no cytotoxic effects were observed.